Development of Pop-Up Book Media on Local Wisdom Material to Improve Global Diversity Attitudes of 4th Grade Students of Sukorejo 2 Elementary School Blitar City - Anggraini, Beti; Alfi, Cindya; Fatih, Mohamad (FKIP - Universitas Riau, 2025)
An attitude of global diversity is a behavior that students must have when implementing an independent curriculum. However, it has been found that students do not understand cultural diversity, especially in their regions. A lack of learning facilities and infrastructure also causes students to lack motivation to participate in teaching activities. This study aims to develop learning tools, it as pop-up books that are valid, appropriate, and interesting for students so it can help to improve global diversity attitude in 4th grade students of Sukorejo 2 Elementary School, Blitar City. This study used a qualitative descriptive research method with the ADDIE development model. Interview, questionnaire, and documentation techniques were used in this research. The study showed that the validation results obtained a score of 96.15% from material experts, 100% from language experts, and 95.45% from media experts. The feasibility level obtained a score of 100% from class teachers. The level of interest got a score of 92.38% and the increase in global diversity attitudes got an N-Gain score of 0.7905 which is included in the high category. Therefore, it can be concluded that pop-up book media is valid, feasible, and interesting. The media can help to improve global diversity capabilities.